Economic growth, tourism and selected macroeconomic variables : a triangular causal relationship in Malaysia - Cheam Chai Li; Rosli Mahmood; Hussin Abdullah; Ong Soon Chuan (2013)
Tourism is one of the largest and fastest growing industries in the world, which makes it a potential strategic factor for economic growth. This adds to the strong interest in the role of tourism in Malaysia’s economic growth as it is the second-largest contributor to foreign exchange earnings after manufacturing. In addition, empirical results associated with Granger causality among economic growth, tourism and exports within the neoclassical framework are inconsistent. The objectives of this study, thus, are to determine: the long-run relationship; the long-run and short-run Granger causality; and the long-run triangular Granger causality between economic growth and tourism receipts corresponding to selected macroeconomic variables such as government tourism expenditure, physical capital, education, health and exports as control variables. The long-run Granger causality in vector error correction model (VECM) shows economic growth, tourism receipts and health complement each other (bidirectional causality), while unidirectional causalities are found between government tourism expenditure, physical capital, education and exports to economic growth. In addition, enhancing physical capital, education, health, exports and government tourism expenditure precede tourism receipts; all these in turn indirectly lead to economic growth, thus witnessing triangular relationships among them.